Kedudukan Konvensi Ketatanegaraan Dalam Sistem Ketatanegaraan Indonesia - Taqiuddin, Habibul Umam (RETORIKA: Journal of Law, Social, and Humanities, 2024)
constitutional system, 2) assess the role of constitutional conventions in supporting order, balance of power, and legal certainty at the national level. This study is a normative legal study that uses a statutory approach, a conceptual approach, and an analytical approach, by examining written norms and the practice of constitutional conventions through legal theory, legal principles, and legal interpretations that include grammatical, systematic, and teleological interpretations. The legal materials used consist of primary, secondary, and tertiary sources, which are analyzed to obtain a comprehensive picture of the position and function of conventions. The results of the study indicate that constitutional conventions have a strategic position as unwritten norms that complement formal regulations and provide guidelines for state institutions in exercising their authority, so that government practices remain consistent with the principles of the rule of law. In addition, conventions play a role in maintaining order between institutions, balancing power, preventing abuse of authority, strengthening the legitimacy of institutional decisions, and guaranteeing legal certainty for the community, thus becoming an important instrument in strengthening the Indonesian constitutional system both from an institutional and legal certainty perspective.